America and a changed world : a question of leadership - Niblett, Robin, 1961- (Chichester, U.K. Wiley-Blackwell, 2010)
'As President Barack Obama attempts to renew America's global leadership, scholars affiliated with Chatham House offer expert perspectives from outside the United States on its ability to continue to play a leading international role. Looking at a range of themes and regions, their analyses provide a challenging basis for rethinking America's international leadership'--
Introduction (Robin Niblett). -- Part I Deepening Regionalism and the US Response -- 1 Latin America: forging partnerships in a transformed region / Victor Bulmer-Thomas -- 2 The Middle East: changing from external arbiter to regional player / Claire Spencer -- 3 Sub-Saharan Africa: providing strategic vision or fire-fighting? / Alex Vines and Tom Cargill -- 4 East Asia: searching for consistency / John Swenson-Wright -- 5 South Asia: navigating minefields / Gareth Price -- 6 Central Asia: responding to the multi-vectoring game / Annette Bohr -- 7 The South Caucasus: drama on three stages / James Nixey -- Part II Partners and Competitors -- 8 China: between global responsibilities and internal transitions / Kerry Brown -- 9 Russia: managing contradictions / James Sherr -- 10 Europe: transatlantic relations still drifting / Robin Niblett -- Part III Global Challenges -- 11 International law and the United Nations: a new era of US engagement / Devika Hovell -- 12 Arms control tomorrow: the challenge of nuclear weapons in the twenty-first century / Paul Cornish -- 13 The United States and climate change: from process to action / Bernice Lee and Michael Grubb with Felix Preston and Benjamin Zala -- 14 The role of the US in the post-crisis economic order / Paola Subacchi -- Index.
Includes bibliographical references and index.
Keywords: United States -- Foreign relations -- 2009-